Roadmap for cardiovascular education across the European Society of Cardiology: inspiring better knowledge and skills, now and for the future - Kotecha, Dipak; Bax, Jeroen J; Carrera, Céline; Casadei, Barbara; Merkely, Bela; Anker, Stefan D; Vardas, Panos E; Kearney, Peter P; Roffi, Marco; Ros, Michelle; Vahanian, Alec; Weidinger, Franz; et al. (Oxford University Press (OUP), 2019)
The provision of high-quality education allows the European Society of Cardiology (ESC) to achieve its mission of better cardiovascular practice and provides an essential component of translating new evidence to improve outcomes.
Keywords: European Society of Cardiology; ESC; education; assessment; skills; knowledge; training; curriculum